AB0424 The effect of high level of anti-citrullinated protein antibodies and rheumatoid factor on bone erosions in patients with early rheumatoid arthritis– a cross-sectional and longitudinal analysis. (15th June 2017) - Yue, J; Griffith, J; Xu, J; Shi, L; Wang, D; Wong, P; Li, EK; Li, M; Li, TK; Zhu, TY; Qin, L; Tam, L-S
Abstract : Background: Bone erosions are a key feature of rheumatoid arthritis (RA) reflecting both disease severity and disease progression. Recent studies using HR-pQCT demonstrated impairment in the bone microstructure of the metacarpophalangeal (MCP) joints of ACPAs-positive healthy individuals despite no signs of arthritis. In patients with established RA, ACPAs and rheumatoid factor (RF) showed an additive effect on erosion number and erosion size. Furthermore, RF influences erosion size only in ACPAs-positive but not in ACPAs-negative patients. Objectives: To determine the effect of high titre of anticitrullinated protein antibodies (ACPAs) and rheumatoid factor (RF) on the number and size of bone erosions in patients with early rheumatoid arthritis (ERA) by high-resolution peripheral quantitative computed tomography (HR-pQCT) at baseline and whether these antibodies are associated with the progression of erosion after one year of follow-up. Methods: In the cross-sectional study, HR-pQCT of the second metacarpophalangeal joint (MCP2) was performed in 124 patients with ERA at baseline, images were analysable in 117 patients. Erosions were visualized in 72 patients and parameters of bone erosions were assessed. In the prospective study, 63 ERA patients who had completed one year of follow-up with repeat HR-pQCT scan were also analysed. The number and volume of the erosions as well as bone mineral density (BMD) surrounding erosion were quantified. Data on demographic and disease-specific parameters including ESR, CRP, DAS 28, ACPAs and RF levels and treatment were recorded. Results: At baseline, 90/117 patients were both ACPAs and RF positive (ACPAs+/RF+ group), 7/117 were only RF (RF+), 13/117 were only ACPAs (ACPAs+) and 7/117 were antibody negative (non-ACPAs+/RF+ group, n=27). Erosion depth and volume were increased in the ACPAs+/RF+ group compared with the non-ACPAs+/RF+ group (both P<0.05) (Table 1 ). Independent explanatory variables associated with a larger erosion volume included RF>16U (P=0.012), older age (P=0.003) and a higher damage joint count (P=0.028). Images from 63 patients who completed 12 months follow-up were analysed. Erosion volume were significantly lower in patients who achieved simplified disease activity score (SDAI) remission at 12 months compared to those who did not (P=0.045). Linear regression analysis indicated that independent predictors for an increase in erosion volume included RF>16U (P=0.032) and a higher damage joint count (P=0.009) at baseline and failure to achieve SDAI remission at 1 year (P=0. 043). Conclusions: ACPAs and RF show an additive effect on erosion volume in ERA patients. Higher RF titre was associated with larger erosion volume at baseline and predicted progression of erosion volume after adjusting for baseline parameters and treatment response. Disclosure of Interest: None declared